Bad Science: Retractions and Media Coverage - Eleonora Alabrese (Center for Economic Studies and ifo Institute (CESifo), 2022)
Flawed research can be harmful both within and outside of academia. Even when published research has been retracted and refuted by the scientific community, it may continue to be a source of misinformation. The media can play an important role in drawing broader attention to research, but may also ensure that research, once retracted, ceases to feature in popular discourse. Yet, there is little evidence on whether media reporting influences the retraction process and authors' careers. Using a conditional difference-in-differences strategy, this paper shows that articles that gained popularity in the media at publication and were later retracted face heavy citation losses, while subsequent citations become more accurate. Further, authors of such papers see a permanent decline in research output. Lastly, the paper provides evidence that media can influence both the likelihood of retraction and its timing, highlighting that the media can play an important role in contributing to the integrity of the research process.
Keywords: 330; science; retractions; media coverage; misinformation; Altmetric; citations; career impact